2018
DOI: 10.3389/fmed.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Salt Sedimentation Assay Does Not Predict Response to Renal Denervation

Abstract: Renal denervation (RDN) has recently been shown to be effective in patients without antihypertensive medication. However, about 30% of patients do not respond to RDN, and therefore, there exists a need to find predictors of response. Individuals are either salt-sensitive (SS) or non-salt-sensitive (NSS) in terms of their blood pressure (BP) regulation. The sympathetic nervous system can influence water and salt handling. RDN reduces sympathetic drive and has an impact on salt excretion. The present study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, increased RSNA results in a reduction of renal blood flow and glomerular filtration rate (GFR), an increase in renal vascular resistance and tubular sodium and water reabsorption, and an increased release of renin, contributing to the development and maintenance of hypertension. Studies performed in patients with therapy resistant hypertension show a robust reduction in blood pressure after renal denervation, highlighting a critical crosstalk between the sympathetic nervous system and the kidney in hypertension (Schlaich et al, 2009;Kandzari et al, 2018;Vonend et al, 2018;Steinberg et al, 2020). In addition, evidence emerges that hypertension is at least in part an immune-mediated inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased RSNA results in a reduction of renal blood flow and glomerular filtration rate (GFR), an increase in renal vascular resistance and tubular sodium and water reabsorption, and an increased release of renin, contributing to the development and maintenance of hypertension. Studies performed in patients with therapy resistant hypertension show a robust reduction in blood pressure after renal denervation, highlighting a critical crosstalk between the sympathetic nervous system and the kidney in hypertension (Schlaich et al, 2009;Kandzari et al, 2018;Vonend et al, 2018;Steinberg et al, 2020). In addition, evidence emerges that hypertension is at least in part an immune-mediated inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…An observation in patients with therapy resistant hypertension have shown a vigorous reduction in blood pressure following renal denervation and thus emphasizes an important crosstalk between the ERSN and the kidney in hypertension. [38,61] In addition findings on single nephron GFR by Bello-Rous and co-workers revealed no change in SNGFR but significant reduction in absolute and fractional Sodium reabsorption in PCT after renal denervation. [62] Similarly, many studies confirmed reduction in solute and water reabsorption in LOH and DCT after renal denervation.…”
Section: Effect Of Renal Nerve Ablationmentioning
confidence: 95%
“…Experimental studies where renal denervation was shown to reduce Blood pressure emphasizes the crucial relationship between sympathetic nervous system and kidney function in chronic diseases like hypertension. [38,39] Animal experimental findings revealed increased renal sympathetic nerve activity, renal sympathetic driven Sodium and water reabsorption, renin release upon reduction in carotid sinus pressure caused by occlusion of carotid artery without altering renal blood flow and GFR. [40,41] Thus the high-pressure baroreceptors are implicated in playing role in hypertension owing to their influence on ERSNA and having the property of resetting its activity at higher arterial blood pressure levels owing to maintenance of renal blood flow and renal function.…”
Section: Concept Of Auto Inhibitory Feedbackmentioning
confidence: 99%